Parenting Styles and Their Association with Developmental Outcomes in Preschool-Aged Children - Ersila, Wahyu; Aisyah , Risqi Dewi; Rofiqoh, Siti; Utami, Susri (Universitas Airlangga, 2026)
Background: Children's growth encompasses stable changes in organ function, from cellular levels to overall bodily development, as well as increases in physical activity, skills, and cognitive processes. Parents' parenting styles significantly influence their child's future development. Objective: This study aims to identify the parenting styles employed by parents concerning motor development, language acquisition, and independence in preschool children at Azzamil School in Pekalongan Regency, Central Java, Indonesia. Methods: A correlational descriptive research design with a cross-sectional approach was utilized. The sample comprised 116 preschool children aged 36 to 60 months and their mothers, selected through a total population sampling technique. Data were collected using a questionnaire designed to assess parenting styles and a Developmental Pre-Screening Questionnaire to evaluate child development. Bivariate data analysis was conducted using the chi-square test. Results: The findings revealed that 87 participants (75%) exhibited democratic parenting styles, while 89 participants (76.7%) demonstrated age-appropriate child development. The statistical analysis yielded a p-value of <0.001, indicating a statistically significant relationship (p < 0.05), with a prevalence ratio (PR) of 8.854 and a 95% confidence interval (CI) of 3.398–23.074. Conclusion: This study concludes that there is a significant relationship between parenting styles and child development. It is recommended that parents utilize nurturing approaches that foster and enhance their children's development through participation in parenting classes.